Hematological and biochemical values of Common Marmoset (Callithrix jacchus) fed with fortified diet (Journal of Laboratory Animal Science, 2022)
The Common Marmoset (Callithrix jacchus) is the smallest non-human primate which is used frequently in biomedical  research. The approximate 88-97% of similarity with human genome makes them a preferable option for use as laboratory  model of human diseases and safety assessment. The present study was undertaken to provide a clinically relevant  reference range for both haematology and serological parameters of Callithrix jacchus at the experimental animal  facility of ICMR-National Institute for Research in Reproductive Health (NIRRH), which houses the largest captive-bred  colony of Common Marmosets in existence. The data also gives the ambient environmental conditions in the laboratory  cages and food supplement with their nutritive values to uphold the healthy colony of marmoset. We have generated an  information from the values obtained in our study of 40 male and 40 female adult Common Marmoset. The hematological  and biochemical values of Common Marmoset (Callithrix jacchus) fed with fortified diet were comparable with values  reported by other researchers. These results will serve as a reference to evaluate the physiological and health status of C.  jacchus populations, which may be useful for further research.
Keywords: Common Marmoset; New World Primate; Animal Model; Hematology; captive-bred